A Preliminary Study of Silver Sodium Zirconium Phosphate Polyurethane Foam Wound Dressing on Wounds of the Distal Aspect of the Forelimb in Horses. Issue 3 (9th July 2014) - Kelleher, Maureen E.; Kilcoyne, Isabelle; Dechant, Julie E.; Hummer, Emma; Kass, Philip H.; Snyder, Jack R.
<x xml:space="preserve">Abstract</x> Objective To determine if application of silver sodium zirconium phosphate polyurethane semi‐occlusive foam (SPF) dressing would improve measures of wound healing and decrease bacterial contamination compared with a non‐adherent, absorbent dressing applied to wounds created on the distal aspect of the equine limb. Study Design Controlled randomized experimental study. Animals Adult Quarter Horse and Thoroughbred horses (n = 5). Methods One 6.25 cm2 wound was created on the dorsomedial aspect of the proximal metacarpus on each forelimb. A SPF dressing was applied to 1 randomly assigned limb as a treatment and a non‐adherent, absorbent dressing was applied to the opposite limb as control. Bandages were changed every 3 days for 60 days. Granulation tissue was scored every 3 days, wound area measured every 6 days, and wound bed was cultured every 12 days. Results SPF‐treatment wounds had significantly decreased wound area and decreased granulation tissue scores when evaluated <30 days and over the 60 day study, although complete wound healing times were not significantly different. Bacteria were cultured from all wounds at varying times throughout the study. Conclusions The SPF wound dressing improved some measures of wound healing compared with the control dressing, most significantly during the first 30 days. This suggests that the SPF wound dressing may be useful in the early management of wounds on the equine lower limb. Further studies using the SPF dressing are needed to characterize the temporal and cellular effects on wound healing and evaluate this dressing in a clinical environment.